Daily Sperm Output, Spermatogenic Efficiency, and Sexual Behavior of Dezhou Donkey Jacks Mounting Jennies in Estrus - Magalhaes, Humberto B.; Canuto, Lucas E.F. [UNESP]; Zhao, Fuwei; Li, Min; Li, Xuexian; Ji, Chuanliang; Canisso, Igor F. (Elsevier, 2021)
This study aimed to assess the sexual behavior of jacks mounting jennies in estrus and determine the daily sperm output (DSO) and spermatogenic efficiency using two equations to calculate testicular volume (TV). Eight sexually rested mature jacks, aging 5 to 10 years old, had semen collected once a day for 10 consecutive days using jennies in good standing estrus for mounting. Sexual behavior and semen parameters were assessed during each collection. Testicular measurements of height, width, and length were taken immediately before the first semen collection, and these measurements were used to calculate TV. After that, the TV was used to predict the DSO. The average total sperm number (TSN) obtained on days 8 to 10 was deemed the actual DSO. Differences in the predicted vs. the actual DSO were used to calculate the spermatogenic efficiency. In addition, the actual DSO was also used to calculate the number of inseminating doses a jack could produce for both on- and off-site breeding. Jack's sexual behavior and sperm motility did not vary across collection days. Sperm concentration and TSN reduced over time (P <.05). The actual DSO was 9.1 ± 4.1 billion, and the predicted DSO varied from 4.7 to 18 billion. Spermatogenic efficiency varied from 50 to 150% based on jack and the equation used to calculate TV. The number of inseminating doses ranged from 15 to 47 at 300-500 million progressively motile sperm (pms)/dose for on-site breeding. In contrast, the number of breeding doses with cooled-shipped semen (1 billion pms/dose) varied from 4 to 14 doses across donkeys. In conclusion, sexual behavior was not affected by daily semen collections. Sexual rest did not affect sperm motility. The predicted DSO varied with the equation used to determine TV. Clinically normal donkeys have high spermatogenic efficiency, which confirms previous histology reports.
Keywords: Daily sperm output; Dezhou donkey; Equus asinus; Sexual behavior; Spermatogenic efficiency